1988
DOI: 10.1002/jsfa.2740450103
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of native and modified lucerne juice for rats

Abstract: An attempt was made to improve the nutritive value of lucerne juice as a protein source for rats. Diets, based on ground barley and lucerne juice, were supplemented with amino acids (methionine andlor lysine), polyethylene glycol (to neutralise phenolic compounds), cholesterol (to neutralise saponins), or fat. In one diet the content of calcium and potassium was lowered. Aerobic fermentation of juice with or without yeasts was also carried out. The biological value ( B V ) and true digestibility ( T D ) of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In particular, for rats whose diet consists of natural ingredients, possible changes in the formulation of these diets may be appropriate to generate improvements in ingredient availability and nutrient composition (Benevenga et al, 1995). Several authors have reported the beneficial effect of supplementing the rat's diet (Van Dam et al, 1999;Rashad and Moharib, 2003;Hanczakowski and Skraba, 2006;Rivera et al, 1978;Taylor et al, 2005). In addition, quinoa provides the diet formulation antioxidant components like vitamin E and phenolic compounds, and constitutes an important energy source (Jørgensen and Lindberg, 2006;Miranda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for rats whose diet consists of natural ingredients, possible changes in the formulation of these diets may be appropriate to generate improvements in ingredient availability and nutrient composition (Benevenga et al, 1995). Several authors have reported the beneficial effect of supplementing the rat's diet (Van Dam et al, 1999;Rashad and Moharib, 2003;Hanczakowski and Skraba, 2006;Rivera et al, 1978;Taylor et al, 2005). In addition, quinoa provides the diet formulation antioxidant components like vitamin E and phenolic compounds, and constitutes an important energy source (Jørgensen and Lindberg, 2006;Miranda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%